Phase transitions in complex functional liquid crystals—The entropy effect - Lehmann, Matthias (Frontiers in Soft Matter, 2023)
Liquid crystal design and synthesis are being driven towards always more complexity. The self-assembly of poly- and shape-amphiphiles allow tailoring the soft material structures with double and even triple nanosegregation of functional building blocks. Alignment of the anisotropic liquid crystal is crucial, in order to generate a full control over the material’s function and performance. This procedure often needs an isotropic phase at accessible temperatures without decomposition. The impact of thermodynamic factors, such as cohesive energy density difference and entropy contributions, is discussed in this perspective paper using selected examples. In the process of molecular design such considerations can help to adjust transition temperatures and subsequently, to achieve aligned, complex liquid crystalline matter. This will allow access to new fields of liquid crystal applications.